Characterizing emergence and divergence in the first follicular wave in a tropically adapted Bos taurus breed - Tortorella, Rodrigo Dorneles; Nogueira, Guilherme de Paula [UNESP]; Modesto, Mairon Rocha; Passoni Silva, Priscilla Cristine; Silva, Joseane Padilha da; Neves, Jairo Pereira; Ramos, Alexandre Floriani (Elsevier B.V., 2017)
Tropically adapted Bos taurus breeds are descended from the cattle which were brought from the Iberian Peninsula to Latin America by the colonizers and which adapted over time to local conditions. These breeds have become a genetic treasure that must be preserved. The objective of this study was to characterize ovarian follicular emergence and divergence in tropically adapted B. taurus cows and heifers. Cyclic heifers (n = 11) and nonlactating, multiparous cows (n = 11) were examined at 8-hour intervals using ultrasonography starting on the day following the final application of PGF(2 alpha), which was used to synchronize the estrous cycle, and ending 5 days after ovulation. Blood samples were collected immediately following the ultrasonographic examinations in order to evaluate FSH and estradiol-17 beta (E-2) concentrations. The interval between ovulation and follicular wave emergence (11.6 +/- 3.3 hours vs. 203 +/- 2.5 hours, P < 0.05) and ovulation and follicular wave divergence (52.4 +/- 5.2 hours vs. 71.8 +/- 4.1 hours, P < 0.05) was shorter in the cows than in the heifers, respectively. Plasma FSH concentrations increased (P.< 0.05) and serum E-2 concentrations decreased earlier in cows than in heifers before ovulation. Following follicular wave emergence, no difference in follicular development was found between the cows and the heifers. Consequently, following follicular wave emergence, the data from both the cows and the heifers were combined and categorized by dominant follicle (DF) and second largest follicle (SF). The DF and SF were identified at the same time (P > 0.05). The mean number of small (<= 4 mm, 7.2 +/- 5.1) and medium (4 to <= 8 mm, 6.8 +/- 3.5) follicles was greater than that of large follicles (>= 8 mm, 0.6 +/- 0.5) from ovulation until 5 days after ovulation. The DF diameter (8.1 +/- 1 mm) did not differ (P = 0.09) from SF diameter (7.6 +/- 0.9 mm) at the time of follicular divergence (around 45 hours after follicular emergence). The DF and SF growth rates were similar (P > 0.05) until follicular divergence, at which point the SF growth rate decreased, whereas the DF growth rate remained constant. Serum E-2 concentrations did not change (P > 0.05) during the divergence period, whereas FSH concentrations decreased between 48 and 32 hours before follicular wave divergence. In conclusion, cows and heifers differed only in the interval from ovulation to follicular wave emergence and divergence, which was confirmed by the different patterns of FSH and E-2 concentrations. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Conservation; Curraleiro Pe-Duro; Dominant follicle; Estradiol 17-beta; FSH